Kajian Setting Time dan Permeabilitas pada Beton Variasi Limbah Granit Sebagai Subtitusi Parsial Agregat Kasar - Fauzy Kurnain; Wibowo Wibowo; Endah Safitri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Currently, infrastructure development is a priority of the Indonesian government which aims to improve the quality of life of the community and equitable distribution of infrastructure development. The need for concrete material as a construction material also increases in line with the increase in infrastructure development. The use of recycled aggregate materials, especially granite waste, is a promising option in sustainable infrastructure development. This study was conducted with the aim of knowing the effect of partial substitution of coarse aggregates using granite waste variations on the binding time and permeability of concrete. Experimental method was chosen in this research. The levels of granite waste used were 0%; 15%; 30%; and 45% by weight of coarse aggregate or gravel. The test specimens used for the concrete bond time study were fresh concrete poured into cube molds measuring 20 cm x 20 cm x 20 cm with a minimum height of 15 cm. Testing concrete bond time using a penetrometer tool. The test specimen for concrete permeability is a cube measuring 15 cm x 15 cm x 15 cm, totaling 12 pieces and tested with a Permeability Test Apparatus (Water Permeabilty Apparatus).The results showed that partial substitution of coarse aggregate with granite waste variation did not affect the setting time of concrete up to a certain level. Based on the results of the research conducted, the initial setting time and final setting time values of 0%, 15%, 30%, and 45% granite content variations fluctuate and the coefficient of determination (R2) value in linear regression is only 0.5 and 0.3. Partial replacement of coarse aggregate with granite waste has an effect on the impermeability of concrete which meets the requirements for medium aggressive impermeable concrete. Water pressure of 5 kg/cm2 for 72 hours applied to the concrete partial replacement of coarse aggregate with granite waste variation resulted in permeability coefficient values of 4.11 x 10-12 cm/s; 3.48 x 10-12 cm/s; 2.17 x 10-12 cm/s; and 3.25 x 10-12 cm/s. The minimum coefficient value of concrete with partial substitution of coarse aggregate with granite waste is obtained at 30% by weight of coarse aggregate. Granite, whose specific gravity is greater than gravel, produces denser and more water-resistant concrete.